Magnetic Connectivity of the Ecliptic Plane within 0.5 au: Potential Field Source Surface Modeling of the First Parker Solar Probe Encounter - Badman, Samuel T.; Bale, Stuart D.; Martínez Oliveros, Juan C.; Panasenco, Olga; Velli, Marco; Stansby, David; Buitrago-Casas, Juan C.; Réville, Victor; Bonnell, John W.; Case, Anthony W.; Dudok de Wit, Thierry; Goetz, Keith; et al. (The Astrophysical journal. Supplement series, 2020)
We compare magnetic field measurements taken by the FIELDS instrument on board Parker Solar Probe (PSP) during its first solar encounter to predictions obtained by potential field source surface (PFSS) modeling. Ballistic propagation is used to connect the spacecraft to the source surface. Despite the simplicity of the model, our results show striking agreement with PSP's first observations of the heliospheric magnetic field from ∼0.5 au (107.5 R ) down to 0.16 au (35.7 R ). Further, we show the robustness of the agreement is improved both by allowing the photospheric input to the model to vary in time, and by advecting the field from PSP down to the PFSS model domain using in situ PSP/Solar Wind Electrons Alphas and Protons measurements of the solar wind speed instead of assuming it to be constant with longitude and latitude. We also explore the source surface height parameter (RSS) to the PFSS model, finding that an extraordinarily low source surface height (1.3-1.5 R ) predicts observed small-scale polarity inversions, which are otherwise washed out with regular modeling parameters. Finally, we extract field line traces from these models. By overlaying these on extreme ultraviolet images we observe magnetic connectivity to various equatorial and mid-latitude coronal holes, indicating plausible magnetic footpoints and offering context for future discussions of sources of the solar wind measured by PSP.